Use of serum levels of high sensitivity troponin T, galectin-3 and C-terminal propeptide of type I procollagen at long term follow-up in heart failure patients with reduced ejection fraction: Comparison with soluble AXL and BNP. (15th December 2016) - Batlle, M.; Campos, B.; Farrero, M.; Cardona, M.; González, B.; Castel, M.A.; Ortiz, J.; Roig, E.; Pulgarín, M.J.; Ramírez, J.; Bedini, J.L.; Sabaté, M.; et al.
Abstract: Background: Prognostic biomarkers are needed to improve the management of the heart failure (HF) epidemic, being the brain natriuretic peptides the most valuable. Here we evaluate 3 biomarkers, high sensitivity troponin T (hs-TnT), galectin-3 (Gal-3) and C-terminal propeptide of type I procollagen (CICP), compare them with a recently described new candidate (sAXL), and analyze their relationship with BNP. Methods: HF patients with reduced ejection fraction (n = 192) were included in this prospective observational study, with measurements of candidate biomarkers, functional, clinical and echocardiographic variables. A Cox regression model was used to determine predictors for clinical events, i.e. all-cause mortality and heart transplantation. Results: Hs-TnT circulating values were correlated to clinical characteristics indicative of more advanced HF. When analyzing the event-free survival at a mean follow-up of 3.6 years, patients in the higher quartile of either BNP, hs-TnT, CICP and sAXL had increased risk of suffering a clinical event, but not Gal-3. Combination of high sAXL and BNP values had greater predictive value (HR 6.8) than high BNP alone (HR 4.9). In a multivariate Cox regression analysis, BNP, sAXL and NYHA class were independent risk factors for clinical events. Conclusions: In this HF cohort, hs-TnT is a good HF marker and has a very significant prognostic value. The prognostic value of CICP and sAXL was of less significance. However, hs-TnT did not add predictive value to BNP, while sAXL did. This suggests that elevated troponin has a common origin with BNP, while sAXL could represent an independent pathological mechanism.